2008
DOI: 10.1002/ana.21390
|View full text |Cite
|
Sign up to set email alerts
|

Spreading depolarizations occur in human ischemic stroke with high incidence

Abstract: CSD and PID occurred spontaneously with high frequency in this study of patients with malignant middle cerebral artery infarction. This suggests that the large volume of experimental studies of occlusive stroke that implicate spreading depolarizations in its pathophysiology can be translated, with appropriate caution, to patients and their treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
373
3
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 393 publications
(390 citation statements)
references
References 41 publications
13
373
3
1
Order By: Relevance
“…We found that inhibition of AMPK using compound-C suppressed SD in 70% of preparations. (Rodgers et al, 2010) that ouabaininduced repetitive SD in the locust resembles peri-infarct depolarizations that prevent the restoration of energy and increase the size of the cortical infarct (Fabricius et al, 2006;Dohmen et al, 2008;Dreier et al, 2009). Given the similarity between locust and mammalian SD phenomena, the modulatory effects of AMPK in our study are highly relevant for understanding the pathology of stroke and seizures.…”
Section: Discussionmentioning
confidence: 84%
“…We found that inhibition of AMPK using compound-C suppressed SD in 70% of preparations. (Rodgers et al, 2010) that ouabaininduced repetitive SD in the locust resembles peri-infarct depolarizations that prevent the restoration of energy and increase the size of the cortical infarct (Fabricius et al, 2006;Dohmen et al, 2008;Dreier et al, 2009). Given the similarity between locust and mammalian SD phenomena, the modulatory effects of AMPK in our study are highly relevant for understanding the pathology of stroke and seizures.…”
Section: Discussionmentioning
confidence: 84%
“…In the case of experimental models, there is new evidence from serial laser speckle flowmetry suggesting that a single depolarization event can propagate for multiple cycles around the periphery of a small cortical lesion (Supplementary video material), giving rise to observation of recurrent, periodic events at a given locus near the edge of the lesion. The possibility arises that similar behaviour might explain periodicity of depolarizations in the injured human brain (Dohmen et al, 2008). This has important implications: studies comparing patient outcome with brain microdialysate glucose levels have suggested that periods of low/zero glucose level are linked to poor outcome (Vespa et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Four centers of the COSBID group conducted a first study in 16 'malignant' stroke patients (Dohmen et al, 2008). In this study, polyphasic slow potential changes of the ECoG (corresponding to the negative slow voltage variation described by Leao (1947) and by Hartings et al (2006) and simultaneous transient ECoG suppressions were recorded as signatures of CSD; slow potential changes in the absence of ECoG background activity were recorded as signatures of PID .…”
Section: Malignant Hemispheric Strokementioning
confidence: 99%
“…An entirely different scenario may apply in the human brain acutely injured for example by ischemic stroke, brain trauma, or subarachnoid or intracerebral hemorrhage (ICH) (Hansen and Lauritzen, 1984;Strong et al, 2002;Fabricius et al, 2006;Dreier et al, 2006;Dohmen et al, 2008). This has been studied recently in patients who underwent neurosurgery including craniotomy because of their acute brain condition, by using cortical electrode strips similar to the technology applied in epilepsy surgery.…”
Section: Introductionmentioning
confidence: 99%